Factors Determining Long-Term Antitumor Responses to Immune Checkpoint Blockade Therapy in Melanoma - Loo, Kimberly; Smithy, James W.; Postow, Michael A.; Betof Warner, Allison (Frontiers in Immunology, 2022)
With the increasing promise of long-term survival with immune checkpoint blockade (ICB) therapies, particularly for patients with advanced melanoma, clinicians and investigators are driven to identify prognostic and predictive factors that may help to identify individuals who are likely to experience durable benefit. Several ICB combinations are being actively developed to expand the armamentarium of treatments for patients who may not achieve long term responses to ICB single therapies alone. Thus, negative predictive markers are also of great interest. This review seeks to deepen our understanding of the mechanisms underlying the durability of ICB treatments. We will discuss the currently available long-term data from the ICB clinical trials and real world studies describing survivorship of ICB treated melanoma patients. Additionally, we explore the current treatment outcomes in patients rechallenged with ICB and the patterns of ICB resistance based on sites of disease, namely liver or CNS metastases. Lastly, we discuss the landscape in melanoma in the context of prognostic or predictive factors as markers of long-term response to ICB.